Impending STEM Shortages in Australia: Beware the 'Smoke and Mirrors'. (8th January 2015) - Panizzon, Debra; Corrigan, Deborah; Forgasz, Helen; Hopkins, Sarah
Abstract: Within Australia over the last decade there has been considerable government rhetoric about impending shortages in the STEM workforce and the long-term impact on the future economy. Much of the data provided in government and industry reports allude to falling participation rates in STEM-related subjects and the inability of industry to employ suitable employees with the necessary skill-sets. In this theoretical paper, we explore these reports and the STEM literature to mine the data so as to highlight the inconsistencies and 'smoke and mirror' messages communicated in many of the findings. Initially, the participation rates of students in STEM-related subjects both at secondary and tertiary levels are explored. Following this, the various disciplines or fields of education comprising STEM are considered. Finally, in order to gain a broader and potentially alternative perspective, economic measures including job availability and salaries are discussed in relation to STEM graduate destinations and employment. While Australia is the context for the discussion, reference is made to emerging data from other countries experiencing similar issues around STEM where applicable.